Analisis Pemasaran Biji Kopi Robusta di Desa Jambuwer Kecamatan Kromengan Kabupaten Malang - Istis Baroh; Moh. Selby Hamzah; Harpowo Harpowo (Universitas Muhammadiyah Malang, 2021)
Indonesia is recorded as the third largest coffee producing country in the world. Robusta coffee is widely cultivated in Jambuwer Village Malang Regency. The purpose of this study was to determine: Robusta coffee marketing channels in Malang Regency. Calculating the amount of marketing margin, margin distribution and share of robusta coffee in Malang Regency. The results of this study indicate that there are four patterns of robusta coffee marketing channels, namely, marketing channel I: Farmers - Wholesalers - Retailers - Consumers. Marketing channel II: Farmers - Middlemen - Resellers - Consumers. Marketing channel III: Farmers - Middlemen - Consumers and marketing channels IV: Farmers - Middlemen - Companies. Meanwhile, the marketing margin for channel I is Rp. 4,000, marketing margin for channel II is Rp. 95,000, channel marketing margin is Rp. 95,000 and channel marketing margin is Rp. 2,000. The farmer's share value in marketing channel I was 84%, marketing channel II was 24%, marketing channel III was 24% and marketing channel IV was 91.7%. The result of the most efficient marketing channel for farmers is the marketing channel IV because it has a low marketing margin and a high farmer share value.